2018
DOI: 10.1177/2325967118789699
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Anterolateral Ligament on Knee Laxity: A Biomechanical Cadaveric Study Measuring Knee Kinematics in 6 Degrees of Freedom Using Dynamic Radiostereometric Analysis

Abstract: Background:An anterior cruciate ligament (ACL) rupture often occurs during rotational trauma to the knee and may be associated with damage to extracapsular knee rotation–stabilizing structures such as the anterolateral ligament (ALL).Purpose:To investigate ex vivo knee laxity in 6 degrees of freedom with and without ALL reconstruction as a supplement to ACL reconstruction.Study Design:Controlled laboratory study.Methods:Cadaveric knees (N = 8) were analyzed using dynamic radiostereometry during a controlled pi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
22
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 71 publications
2
22
0
2
Order By: Relevance
“…Schon et al 29 looked at 7 different graft fixation angles from 0 to 90 with 88 N of tension and found that there was no difference in knee kinematics based on fixation angle, but they did note overconstraint at all fixation angles. Geeslin et al 11 also noted overconstraint at differing fixation angles, even with lower graft tensions of 20 N and 40 N, which is in contrast to multiple studies 5,15,16,23,30 that showed no overconstraint at lower fixation tensions. Although the clinical relevance of overconstraint remains to be determined, a way to prevent it may be to perform ALLR at lower fixation angles and tensions.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Schon et al 29 looked at 7 different graft fixation angles from 0 to 90 with 88 N of tension and found that there was no difference in knee kinematics based on fixation angle, but they did note overconstraint at all fixation angles. Geeslin et al 11 also noted overconstraint at differing fixation angles, even with lower graft tensions of 20 N and 40 N, which is in contrast to multiple studies 5,15,16,23,30 that showed no overconstraint at lower fixation tensions. Although the clinical relevance of overconstraint remains to be determined, a way to prevent it may be to perform ALLR at lower fixation angles and tensions.…”
Section: Discussionmentioning
confidence: 93%
“…Although there have been clinical studies 5 , 7 , 8 , 17 , 29 , 32 that support combined reconstruction, there are biomechanical studies that do and do not recommend a combined approach. 11 , 15 , 16 , 23 , 29 , 30 The purpose of this study was to perform a systematic review and meta-analysis of biomechanical data to evaluate the kinematic changes of a combined ACLR/ALLR compared with isolated ACLR as well as to assess the effects of different fixation techniques.…”
mentioning
confidence: 99%
“…Smatra se da udružena rekonstrukcija ACL-a i ALL-a sprječava pojavu rotacijske nestabilnosti i pridonosi ukupno boljoj stabilnosti koljena 20,21 . Iako su u studiji rađenoj na kadaverima Schon i suradnici upozorili na mogući rizik od prekomjernog ograničenja unutarnje rotacije koljena nakon rekonstrukcije ALL-a, takve su tvrdnje nedavno osporene dokazom da rekonstrukcija ALL-a ne dovodi do prekomjernog opterećenja zgloba koljena 20,22,23 . Značajna razlika u odnosu na tehnike koje su se upotrebljavale 1990-ih godina u današnjoj tehnici rekonstrukcije ACL-a i ALL-a je u pozicioniranju ALL-ova tunela na bedrenoj kosti (slika 3) i fiksaciji ALL-presatka u punoj ekstenziji koljena i neutralnoj rotaciji potkoljenice, što smanjuje mogućnost razvoja komplikacija i neželjenih ishoda 5 .…”
Section: Anatomija All-aunclassified
“…Također je pokazano i da je udružena rekonstrukcija ACL-a i ALL-a povezana sa znatno većom vjerojatnošću povratka na istu razinu sportske aktivnosti kao i prije ozljede 24 . Prevelika napetost presatka ALL-a i dalje predstavlja izvor rasprava, ali se pokazalo da rekonstrukcija ALL-a, s položajem fiksacije neposredno proksimalno i straga u odnosu na lateralni epikondil bedrene kosti i zatezanjem u punoj ekstenziji koljena, može vratiti normalnu kinematiku koljena bez dodatnog opterećenja na lateralni odjeljak koljena 23 . Važno je napomenuti da udružena rekonstrukcija ALL-a uz rekonstrukciju ACL-a ne povećava rizik od postoperativnih komplikacija.…”
Section: Udružena Rekonstrukcija Acl-a I All-a I Klinički Ishodiunclassified
“…Condition-numbers ensured a high-quality MM reference. We used previously validated methods of placing ACS based on bone geometry 24,32. Results from theBM are expressed in clinically relevant terms through inheritance use of ACS.…”
mentioning
confidence: 99%